Online Vulnerability Assessment in Cascading Failure Analysis Using an Intelligence Monitoring Model - Saber Armaghani; Zahra Moravej (مجله مدل سازی در مهندسی)
Today, the Special Protection Scheme usage has been proposed as an effective and efficient strategy to reduce the impact of disturbance and avoid the occurrence of blackouts of the transmission network, which has different tasks. One of the tasks of the Special Protection Scheme is to develop a corrective control action to prevent the occurrence of long-term voltage instability. In this paper, a new model is proposed in the Special Protection Scheme for long-term under-voltage load shedding, which is based on minimizing the shedding cost and power losses in power systems, modeling voltage-dependent loads, load response model, and considering feeders. The economic and technical considerations in the proposed model play an essential role in the characteristics of the Special Protection Scheme for under voltage load shedding. Thus, in this paper, Demand Response modeling will be based on determining the cost of electric energy consumption in the emergency of the network in such a way as to cause a shift of consumption to improve the performance of the network. Since load feeders and load response are considered in this paper, the mentioned problem is defined in the form of discrete-continuous optimization to determine the location and amount of necessary load removal as well as the amount of load transfer between the load buses to establish long-term voltage stability in the transmission network using discrete and continuous particle swarm algorithm. The proposed model has been simulated in the standard IEEE 57-bus test system to determine and prove the effectiveness of the proposed Special Protection Scheme for load shedding.